Gestational age, birth weight, and infant 1-year mortality risk: A large-scale analysis of 6.9 million births from the Japanese National registry - Miho Sassa; Ayaka Monoi; Yayoi Murano; Utako Kondo; Hiromichi Shoji; Daisuke Yoneoka (PLoS ONE, 2025)
Background Japan’s low infant mortality rates (IMR) reflect advancements in neonatal care. However, a comprehensive understanding of factors influencing long-term infant mortality nationwide is lacking. We examined the 1-year relationships between gestational age (GA), birth weight, small-for-gestational-age (SGA) status, and infant mortality risk. Objective This study aimed to estimate the 1-year survival probability of infants stratified by GA, birth weight and SGA status. Methods This study is an observational study using Japan’s vital registration data between 2012 and 2018. Whole national birth and death registration data was analyzed. 6,918,305 births and 12,440 deaths within the first year of age were included. The main outcome is 1-year infant mortality and survival curve. Results Infants born preterm, and SGA exhibited elevated mortality rates (15 and 8.5 per 1,000, respectively). Survival probability varied significantly based on GA, birth weight, and SGA status. Overall 1-year mortality risk was 1.8 per 1,000 live births with survival probabilities notably increasing with GA. Late preterm and early term births also exhibited increased mortality risks compared to full term infants (e.g., 2.2 per 1,000 live births if born at 37 weeks vs 0.76 at 39 weeks). Notably, late preterm births constituted the majority of preterm births and were associated with major mortality risks. Conclusions This study, extending beyond previous short-term research, provides insights into long-term infant mortality risks in Japan, underscoring the importance of gestational age, birth weight, and SGA status in infant mortality risk among live births. Further study to elucidate the reasons behind pregnancy termination decisions and the specifics of antenatal and neonatal care is needed to better understand the factors influencing infant mortality.